MILITER DALAM AL-QUR’AN: Relevansi Konsep Militer Nabi Muhammad SAW dan Implementasinya dalam Kepemimpinan Tentara Nasional Indonesia - Syarifuddin Muhammad (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2020)
This article presents the leadership of Prophet Muhammad PBUH in the field of military that has relevance to the Indonesian National Army as reflected in his actions and behaviors, which are highly spirited, brave and intelligent, militant, strong and skilled and his role model as a perfect individual. In leading the military, Muhammad PBUH prioritized ethics in battles and efforts for self defense. This is different from, example the style of military leadership of Hitler and Genghis Khan who tended to use any means to materialize their ambition to control a region. The perspective of the Qur’an and hadith on the military ethics of the Prophet is found in several characteristics, among others: 1) obedient and loyal to Allah the God, His Messengers, leaders and the people; 2) Commitment by mutual agreement with other parties; 3) Defending the oppressed; 4) Not damaging public facilities; 5) Not damaging historical sites; 6) Not killing the elderly, children and the surrendered. The interpretation method used in this study is the method of maudhu’i interpretation and the historical-critical-contextual method. While the approach used is qualitative approach. Qualitative approach is used to produce descriptive data which results are presented in the form of qualitative.